1998
DOI: 10.1590/s0066-782x1998000200008
|View full text |Cite
|
Sign up to set email alerts
|

Associação entre diferentes indicadores de obesidade e prevalência de hipertensão arterial

Abstract: Purpose -To evaluate the association between body mass index (BMI), waist-hip ratio and waist circumference with the prevalence of hypertension in a representative (RR 1,9, IC 1,(0)(1)(2)(3)2 masculino; RR 2,2, IC 1,8 feminino

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1
13

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 13 publications
4
12
1
13
Order By: Relevance
“…In relation to blood pressure, we did not find any differences Arq Bras Cardiol 2006; 87(6): 666-671 between genders, both for DBP and SBP, in disagreement with the results of Guedes & Guedes 25 and Gus et al 30 , which showed higher blood pressure levels among men.…”
Section: Discussioncontrasting
confidence: 99%
“…In relation to blood pressure, we did not find any differences Arq Bras Cardiol 2006; 87(6): 666-671 between genders, both for DBP and SBP, in disagreement with the results of Guedes & Guedes 25 and Gus et al 30 , which showed higher blood pressure levels among men.…”
Section: Discussioncontrasting
confidence: 99%
“…Neste sentido, as medidas de controle e prevenção dos riscos modificáveis para a população estudada estão situadas na esfera da adoção de estilo de vida e da alimentação saudável, ainda que não tenha sido encontrada associação entre estas variáveis incluídas no modelo e o excesso de peso e/ou gordura abdominal. Estas são reconhecidas como estratégias capazes de reduzir a expressiva parcela das mortes prematuras e o impacto negativo na qualidade de vida dos indivíduos 33 , atributos que podem também ser destacados para o sobrepeso enquanto evento que precede a obesidade. …”
Section: Discussionunclassified
“…Therefore, waist circumference was used, because in addition to being inexpensive and easy to obtain, it is a known risk factor for circulatory system diseases and diabetes mellitus 23 .…”
Section: Discussionmentioning
confidence: 99%